Cloris [large type] : my autobiography - Leachman, Cloris (Thorndike Press large print biography series, 2009)
She received two Emmy Awards as Phyllis on The Mary Tyler Moore Show, an Oscar for her role in The Last Picture Show, and delighted audiences as Frau Blucher in Young Frankenstein and Nurse Diesel in High Anxiety. But who, really, is Cloris Leachman? She's one of the most acclaimed and unpredictable actresses of our time. Now, for the first time, Cloris reflects on her amazing life and illustrious career.